The Ethics of Effective Teaching: Challenges from the Religious Right and Critical Pedagogy - Trelstad, Marit (Teaching theology and religion, 2008)
This essay asks: What are the ethics of engaging self-identified “conservative” students in topics and processes of learning that may unravel their world-view and possibly their personal lives? We should take their concerns, fear, and distrust seriously and not simply dismiss them as ignorant. We should strive to be “trustworthy” educators, guiding students through the consequences of transformative education. This paper argues that conservative students are critically examining and reacting to the liberal academy by leveling critiques similar to those found within feminist, post-colonial and post modern pedagogies. This essay reviews contemporary postmodern, postcolonial, and feminist pedagogies, which analyze bias and power in the classroom and have sought to represent marginalized voices in the classroom in order to challenge the way education often simply serves and protects the interests of the privileged. Pedagogies centered on subject or disciplinary method cannot secure a trustworthy pedagogy since method, thinking skills, and subjects are themselves bias-laden. But critical pedagogy offers insights to help us achieve the goal of becoming trustworthy educators for students coming from a wide spectrum of religious perspectives.